2013
DOI: 10.1186/1471-2458-13-974
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention of overweight in preschool children, the BeeBOFT study (breastfeeding, breakfast daily, outside playing, few sweet drinks, less TV viewing): design of a cluster randomized controlled trial

Abstract: BackgroundTwo overweight prevention interventions were developed to be offered by preventive Youth Health Care (YHC) in addition to the currently applied overweight prevention protocol to parents of 0-3 year old children. The two interventions aim to support parents of preschool children to realize healthy child nutrition and activity behaviors of their young child. The aim of this study is to assess the effects of the two overweight prevention interventions with regard to child health behaviors and child Body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 21 publications
0
47
0
Order By: Relevance
“…(19)In fact, increasing young children’s sleep is considered amongst the most promising strategies for reducing childhood obesity. (20-22) Mechanisms are similar to those for SDB, (1-4) but also include effects upon biological (circadian) and social (household) rhythms. (2, 3) In recent years, short sleep duration has eclipsed SDB as a putative risk factor in the literature on childhood obesity.…”
mentioning
confidence: 96%
“…(19)In fact, increasing young children’s sleep is considered amongst the most promising strategies for reducing childhood obesity. (20-22) Mechanisms are similar to those for SDB, (1-4) but also include effects upon biological (circadian) and social (household) rhythms. (2, 3) In recent years, short sleep duration has eclipsed SDB as a putative risk factor in the literature on childhood obesity.…”
mentioning
confidence: 96%
“…Positive association between consumption of sugar-sweetened beverages (SSBs) and overweight/obesity has frequently been addressed in earlier literature [24,25], but few studies have considered all types of beverages, including water intake. Some prior investigations have reported that only sugar-sweetened beverages, out of all drinks, were linked to the risk of obesity [24].…”
Section: Discussionmentioning
confidence: 99%
“…12 The themes were categorized from the content analysis 13 in: Food practices healthy; Prevention of overweight and obesity; Food and nutrition security. It is described among the 17 articles in the final sample, 15 were written in the English language; [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] one in Spanish 23 and one, in Portuguese. 26 As regards the year of publication, three were published in 2017; 20 three in 2016; 16,19,23 two, in 2015, 17,24 three, in the year 2013; 18,21,25 four, in 2012 22, and two, in 2011.…”
Section: Introduction Methodsmentioning
confidence: 99%